PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA SMAN 2 TAMBANG - Rezki Hidayat; Maria Erna; R Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research on the application of the Think Pair Share (TPS learning model has been done to improve students learning achievement in the topics of chemical bonding in class X MIA SMAN 2 Tambang. This research is experiment based on pretest-posttest design. The sample consisted of two classes, which are X MIA 1 as experiment class and X MIA 2 as control clas that randomly selected after testing normality and homogeneity. Experiment class is a class that is treated by applying the Think Pair Share (TPS learning model. Analyzed of data used t-test. Results of the analysis it was found that tscore>ttable (2,235>1,67), it means the Think Pair Share (TPS learning model can improve students learning achievement on the chemical in class X MIA SMAN 2 Tambang with an increase of 6,7%.Key Words: Research on the application of the Think Pair Share (TPS learning model,learning achievement